Turkish teachers’ values with rational and non-rational truth and teacher emotions in teaching - Ünal, Kübra; Myyry, Liisa; Toom, Auli (Frontiers in Psychology, 2024)
The aim of this study was to clarify the relationships between personal values, truth-related values and emotions among Turkish teachers. The Schwartz’s Value Theory and Frenzel’s teacher emotion model were used as the theoretical framework. This study used a cross-sectional correlational research design. The data were collected from 279 teachers with the Portrait Value Questionnaire (PVQ) where rational truth and non-rational truth values were added, and with the Teacher Emotions Scale (TES). The circular structure of the Schwartz Value Theory was tested by multidimensional scaling. The data analysis aimed to uncover relationships between personal values, truth-related values, and emotions. Rational truth emerged near self-direction and self-transcendence, yet items measuring non-rational truth were scattered among values. Females had higher regard for self-direction and hedonism than males. Non-rational truth was negatively correlated with enjoyment, while it was positively correlated with anxiety. The implications for gender roles in Turkish society are discussed.